A New Part-Metric-Related Inequality Chain and an Application - Xiaofan Yang; Fangkuan Sun; Yuan Yan Tang (Discrete Dynamics in Nature and Society)
Part-metric-related (PMR) inequality chains are elegant and are useful in the study of difference equations. In this paper, we establish a new PMR inequality chain, which is then applied to show the global asymptotic stability of a class of rational difference equations.